The role of toll-like receptor 9 in chronic stress-induced apoptosis in macrophage. - Yanxiao Xiang; Hui Yan; Jun Zhou; Qi Zhang; Gregory Hanley; Yi Caudle; Gene LeSage; Xiumei Zhang; Deling Yin (PLoS ONE, 2015)
Emerging evidence implied that chronic stress has been exerting detrimental impact on immune system functions in both humans and animals. Toll-like receptors (TLRs) have been shown to play an essential role in modulating immune responses and cell survival. We have recently shown that TLR9 deficiency protects against lymphocyte apoptosis induced by chronic stress. However, the exact role of TLR9 in stress-mediated change of macrophage function remains unclear. The results of the current study showed that when BALB/c mice were treated with restraint stress (12 h daily for 2 days), the number of macrophages recruited to the peritoneal cavity was obviously increased. Results also demonstrated that the sustained effects of stress elevated cytokine IL-1β, TNF-α and IL-10 production yet diminished IFN-γ production from macrophage, which led to apoptotic cell death. However, TLR9 deficiency prevented the chronic stress-mediated accumulation of macrophages. In addition, knocking out TLR9 significantly abolished the chronic stress-induced imbalance of cytokine levels and apoptosis in macrophage. TLR9 deficiency was also found to reverse elevation of plasma IL-1β, IL-10 and IL-17 levels and decrease of plasma IFN-γ level under the condition of chronic stress. These results indicated that TLR9-mediated macrophage responses were required for chronic stress-induced immunosuppression. Further exploration showed that TLR9 deficiency prevented the increment of p38 MAPK phosphorylation and reduction of Akt/Gsk-3β phosphorylation; TLR9 deficiency also attenuated the release of mitochondrial cytochrome c into cytoplasm, caused upregulation of Bcl-2/Bax protein ratio, downregulation of cleavage of caspase-3 and PARP, as well as decreased TUNEL-positive cells in macrophage of stressed mice. Collectively, our studies demonstrated that deficiency of TLR9 maintained macrophage function by modulating macrophage accumulation and attenuating macrophage apoptosis, thus preventing immunosuppression in restraint-stressed mice.